Time to Effective Ventilation in Neonatal Manikins with a Supraglottic Airway vs. a Facemask: A Randomized Controlled Trial - Nithya Sivakumar; Shoshana Newman-Lindsay; Deepika Sankaran; Satyan Lakshminrusimha; Lee Donohue (MDPI AG, 2023)
(1) Background: Timely and effective positive pressure ventilation (PPV) is the most important component of neonatal resuscitation. Emerging data supports the use of supraglottic airways such as the laryngeal mask airway (LMA) as a first-line interface for PPV during neonatal resuscitation. LMA use reduces the need for intubation compared to facemask use in systematic reviews, but there is no difference in the incidence of death or moderate-to-severe hypoxic ischemic encephalopathy (HIE). Time to effective ventilation during simulation with manikin models by providers with limited neonatal airway experience may add to the current evidence that compares the LMA to the neonatal facemask as the first-line ventilation interface during neonatal resuscitation.; (2) Methods: Thirty-two pre-clinical medical students were recruited and randomized to learning and performing ventilation with either the LMA or neonatal facemask on a neonatal manikin. Tidal volume was measured by breath-by-breath analysis to assess adequacy and consistency of PPV in 10 consecutive breaths. Perceived confidence was measured by pre- and post-intervention surveys that utilized a Likert scale from 1 to 5.; (3) Results: Median time to achieve effective ventilation was shorter with a neonatal facemask compared to the LMA (43 (30, 112) seconds vs. 82 (61, 264) seconds, p < 0.01). Participants reported higher perceived confidence post-intervention with use of a facemask when compared to use of the LMA (5 (4, 5) vs. 4 (4, 4), p = 0.03).; (4) Conclusions: Pre-clinical medical students demonstrated a shorter time to effective ventilation and reported higher confidence scores after learning and demonstrating PPV using the facemask when compared to LMA in a neonatal manikin. Further studies are warranted to evaluate the use of supraglottic airways in providers with limited experience with airway management of neonates, as well as in ways to better promote proficiency and confidence in the use of the LMA.